Job Satisfaction of Workers: An Empirical Study in the Manufacturing Sector of Punjab - Ahluwalia, Amardeep Kaur; Preet, Kamal (Prabandhan: Indian Journal of Management, 2015)
Job satisfaction refers to a positive attitude of people towards their job or work. The present study was conducted to explore the factors that are responsible for satisfaction among workers working in the manufacturing industry in the state of Punjab. The study was conducted in Amritsar and Ludhiana districts in Punjab. Various determinants of satisfaction with regard to competitive salary, possibility of growth, administrative regulations, and so forth were discussed in the study. Theories of motivation were also discussed, which were linked to various factors of job satisfaction among workers. A sample of 170 workers (80 men workers and 90 women workers) participated in the study. By using the t -test, significant differences were found among the men and women workers with respect to various items that affected their job satisfaction levels.